Network Analysis of Eight Technological Systems - Riccardo Leoncini; S. Montresor (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1998)
The systemic nature of technological change is now a well established result of much literature, of both theoretical (e.g. Carlsson & Stankiewicz, 1991; Lundvall, 1992; De Liso & Metcalfe, 1996; Edquist, 1997) and empirical (e.g. Nelson, 1993; Patel & Pavitt, 1994; Saxenian, 1994; Carlsson, 1995) nature. As the innovative process does not follow a 'linear', isolated path, but occurs within specific institutional contexts of interactive relationships between different organisations, concepts such as those of innovative and technological systems appear to be the most appropriate units of analysis. However, several specifications have been provided, by referring to both functional and geographical boundaries, which are differently characterised and thus determine differences in the level of analysis and in methodologies. As far as this paper is concerned, we will adopt a broad and structured notion of technological system that we deem particularly suitable to retain relationships that are not only innovative as such, but also techno-economic—i.e. related not only to the functioning of the innovative and of the production sub–systems, but also of the market (both domestic and foreign) and the institutional infrastructure. footnote Furthermore, our definition refers to national technological systems, because we claim that, even in a world of increasing globalisation and localisms, national boundaries still matter: for example, interesting idiosyncrasies and clusters emerge by looking at the 'configurations' that technological systems assume in different countries (Leoncini & Montresor, 1998). This paper aims at measuring and comparing some of the key relationships within a technological system by considering its intersectoral techno–economic linkages. footnote We thus intend to highlight the role of innovative flows of different magnitude within it, the location of its 'cores' and 'terminals', the inward or outward configuration of its partitions, from both a 'cross–sectional' and a 'time series' comparative perspective. The application refers to eight OECD countries along three temporal spans (see Appendix A1 for full details). It consists of a network analysis of the intersectoral innovation flows matrices we have obtained by disaggregating each technological system into 15 manufacturing sectors (Appendix A2). The paper is organised as follows. In Section 2 the methodological issues about innovation flows matrices and network analysis are briefly reviewed. Section 3 describes the empirical results. Section 4 contains the main conclusions.
Keywords: 330